Behavioural Biases in Investment Decision-Making: A Review, Synthesis and Future Research Agenda (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study of behavioural finance has garnered significant interest from many researchers, showing a growing trend in the publication of research articles in recent times. This paper presents a systematic review and bibliometric analysis of the existing literature in the field of behavioural finance. The study utilized RStudio and VOS viewer software to perform a bibliometric analysis of data retrieved from the Scopus database following the PRISMA protocol. It also systematically reviewed existing literature to identify key behavioural biases, methodologies, and findings of the selected articles. The findings reveal a growing trend in the publication of research articles, the most impactful authors and journals, the most frequently used keywords, and the top contributing countries and organizations. The paper concludes by suggesting a future research agenda based on the research gaps identified after reviewing the selected studies.